The African Diaspora in Canada Negotiating Identity and Belonging - Tettey, Wisdom J.; Puplampu, Korbla P. (Africa: Missing Voices, 2006)
This book addresses the conceptual difficulties and political contestations surrounding the applicability of the term "African-Canadian." In the midst of this contested terrain, the volume focuses on first-generation, black continental Africans who have immigrated to Canada in the last four decades, and have traceable genealogical links to the continent. The rationale behind highlighting the experiences of the first generation of African immigrants within Canadian society is to address the empirical, conceptual, and methodological gaps in the literature that tends to homogenize all black people and their experiences. The book, thus, seeks to highlight the peculiar characteristics of continental Africans which may not be shared by other blacks or non-black Africans. The chapters examine the social constructions of African-Canadians and their experiences within the political and educational systems, as well as in the labour market. They also explore the forms of cooperation and tensions that characterize the communities, and how they negotiate and adapt to the multiple transnational spaces that they occupy. The book also explores the circumstances of their children, as they try to define their identities vis-à-vis their parents and the larger Canadian society.